NANOPARTIKEL EMAS DALAM PRODUK KOSMETIK: PENELITIAN AWAL DARIPADA PERSPEKTIF MAQĀṢID AL-SHARĪ‘AH: Gold Nanoparticles in Cosmetic Products: A Preliminary Study from The Perspective of Maqāṣid al-Sharī‘ah - Che Mohd Rashid, Nurul Ainna; Kamri, Nor 'Azzah; Pauzi, Norhidayah (Jurnal Syariah, 2025)
Gold is a highly valuable metal with diverse functions. Currently, gold is widely used in various fields, including cosmetics such as gold nanoparticles in skincare products. Therefore, the use of gold nanoparticles in facial cleansers, scrubs, and serums has sparked debate in fatwa institutions related to the cosmetics industry. However, the use of gold nanoparticles carries both benefits (maslahah) and harms (mafsadah) that require evaluation. Thus, this study aims to conduct preliminary research on the use of gold nanoparticles in cosmetic products based on the maqāṣid al-sharī‘ah framework, particularly focusing on the maslahah and mafsadah of their usage. For this purpose, the study employs a qualitative approach to gather literature and fatwas related to gold. This is followed by a content analysis focusing on two main themes: the maslahah and mafsadah of using gold in cosmetic products. The findings from previous studies highlight the general effects of using gold nanoparticles, which include significant benefits (maslahah) such as anti-aging properties, alongside its harms (mafsadah) such as potential health risks. However, the permissibility status issued by the Federal Territories Mufti Department and the Indonesian Ulama Council emphasizes the element of benefits (maslahah) in determining the hukm on the use of gold nanoparticle-based cosmetics for men. The study, grounded in maslahah and mafsadah, as well as textual (naqli) and rational (‘aqli) evidence, is crucial to establish authoritative guidance for the welfare of the ummah and the sustainability of the halal cosmetic industry.